Production and decomposition of mangrove litter in Jang River Estuary, Bukit Bestari District, Tanjungpinang City - Gusti Randa; Febrianti Lestari; Dedy Kurniawan (Samakia : Jurnal Ilmu Perikanan, 2020)
The purpose of this study was to analyze the level of mangrove density, the level of production and decomposition of mangrove litter in Jang River Estuary, Bukit Bestari District, Tanjungpinang City. Determination of the research location using purposive sampling method based on development activities around the Muara Jang River mangrove area, including the area of ​​community settlement development (station 1), landfill area for the construction of shop houses and housing (station 2) and the area without development activities (station 3). To measure the density of mangroves using a plot of 10 x 10 m2 with 3 plots, to measure the production of mangrove litter using litter and to measure the decomposition of mangroves using litter with a 0.5 cm mesh size placed under mangrove trees that are still affected by tides. The results showed the level of mangrove density at station 1 was 1033 ± 51 trees/ha with good criteria and moderate density, station 2 was 933 ± 115 trees/ha with rare damage and density criteria, and station 3 was 1367 ± 208 trees/ha with good criteria and moderate density. The level of mangrove litter production at Station 1 is 5.14 grams dry weight / m2, Station 2 is 2.80 grams dry weight / m2, and Station 3 is 6.67 grams dry weight / m2. The mangrove decomposition rate at station 1 was 63.33%, station 2 was 62.05% and station 3 was 67.73%.